Science Studentsâ€™ Spontaneous Utilization of School Library with Logistic Growth Model: A Focus on Gender - Obasi, Chinedu Victor (Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
In this paper the logistic growth model of spontaneous utilization of school library in Imo State, is presented. Firstâ€order variables separable logistic equation is solved. The parameters that gave the best logistic curve for the data were determined. The number of male and female science students who utilized school library spontaneously also is presented. The logistic equation allows rigorous estimation of 2.34% growth rate of male science studentsâ€™ spontaneous utilization of school library in Imo State. While that of female students is decreasing by 2.71%. The results revealed that male students are experiencing upward trend in the spontaneous utilization of school library while their female counterparts are experiencing downward trend. Therefore, it is recommended that science students should utilize the school library resources spontaneously without being induced to do so. They should also develop passion for reading because reading books pushes readers to use their imaginations and encourages creativity for scientific endeavours.